1988
DOI: 10.1007/bf01116460
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hepatic cholesterogenesis by polar steroids accumulated after cholesterol feeding

Abstract: The incorporation of mevalonate into nonsaponifiable lipids by chick liver in vivo strongly increased between 1-18 days after hatching. Cholesterol feeding (2%) inhibited this. Synthesis of cholesterol was strongly inhibited, whereas the intermediates isolated by TLC accumulated. Most of the polar nonsaponifiable lipids that accumulated in liver 90 minutes after mevalonate administration to 18-day-old cholesterol-fed chicks were identified as lanosterol derivatives. 3-Hydroxy-3-methylglutaryl-CoA reductase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Bars with an asterisk are significantly higher (P<05) than those without cholesterol on the same day for chicks from the same laying hen diet terol pool of chicks at hatching. It is known that large body cholesterol pool in the cholesterol-fed animals tends to increase bile acids formation and reduce cholesterol synthesis (Wilson, 1964;Aguilera et al, 1988). The present study showed that cholesterol feeding to laying hens (maternal diet) influenced cholesterol metabolic pathways in developing animals.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Bars with an asterisk are significantly higher (P<05) than those without cholesterol on the same day for chicks from the same laying hen diet terol pool of chicks at hatching. It is known that large body cholesterol pool in the cholesterol-fed animals tends to increase bile acids formation and reduce cholesterol synthesis (Wilson, 1964;Aguilera et al, 1988). The present study showed that cholesterol feeding to laying hens (maternal diet) influenced cholesterol metabolic pathways in developing animals.…”
Section: Discussionmentioning
confidence: 66%
“…The conversion of cholesterol into bile acids is the chief pathway for cholesterol catabolism, and 7-oc-hydroxylase is the key enzyme controlling this pathway (Danielsson and Sjovall, 1975). Feeding cholesterol to adult animals usually inhibits the cholesterol de novo synthesis and increases the production of bile acids (Wilson, 1964;Siperstein and Fagan, 1966;O'Brien et al, 1977;Aguilera et al, 1988). Theoretically, when a developing animal is exposed to a cholesterolrich environment, the cholesterol metabolism pathway can be influenced in the same way as The four treatments were high cholesterol (CH) laying hen diet-high CH starter diet (Hm-Hs); high CH layer's diet-low CH starter (Hm-Ls); Low CH layer's-high CH starter (Lm-Hs); and low CH layer's-low CH starter (Lm-Ls).…”
Section: Discussionmentioning
confidence: 98%
“…The same dietary manipulation induced a significant inhibition not only of HMG-CoA reductase activity 40 but also of mevalonate incorporation into total nonsaponifiable lipids, 17,35 as well as in mevalonate 5-pyrophosphate decarboxylase activity. 44 A fraction of lanosterol derivatives and cholesterol precursors accumulated after cholesterol feeding may be responsible for the HMG-CoA reductase inhibition 45,46 as well as for the decrease of cholesterol synthesis from mevalonate. 46 Diminution of these nonsaponifiable lipids in chick liver between 5 and 11 days of postnatal development also may explain the clear increase of HMG-CoA reductase activity found during the same neonatal period.…”
Section: Discussionmentioning
confidence: 99%
“…44 A fraction of lanosterol derivatives and cholesterol precursors accumulated after cholesterol feeding may be responsible for the HMG-CoA reductase inhibition 45,46 as well as for the decrease of cholesterol synthesis from mevalonate. 46 Diminution of these nonsaponifiable lipids in chick liver between 5 and 11 days of postnatal development also may explain the clear increase of HMG-CoA reductase activity found during the same neonatal period. 47 It has been reported that cholesterol biosynthesis is suppressed in mammalian cells by the addition of whole serum to the culture medium.…”
Section: Discussionmentioning
confidence: 99%